Development of mid-infrared light-emitting diodes for low-power optical gas sensors - Meriggi, L.; Steer, M.; Ding, Y.; Thayne, I.; MacGregor, C.; Ironside, Charlie; Sorel, M. (2015)
This work presents the experimental investigation of different techniques to improve the electrical and optical performance of mid-infrared antimonide-based semiconductor light-emitting diodes. A study of the current crowding effect, supported by spatially-resolved photocurrent measurements, allows the design of an optimal contact geometry. Additionally, a higher fraction of the generated light is redirected towards the top surface of the device thanks to the integration of a back reflector and a resonant-cavity design. Enhanced performance for mid-IR LEDs represents a significant step forward towards power efficient optical sensors for environmental, safety and health applications.